Umbilical Artery Doppler Findings in Patients with Preterm Premature Rupture of Membranes - Oya Aldemir; Ertuğrul Karahanoğlu; Deniz Esinler; Neslihan Yerebasmaz; Erdem Fadıllıoğlu (Medical Network, 2016)
OBJECTIVE: Comparison of umbilical artery hemodynamic parameters in Preterm Premature Membrane Rupture of Membrane (PPROM) cases with healthy control group STUDY DESIGN: This study was performed as a retrospective cohort study at Ankara Etlik Zubeyde Hanım Maternity Hospital among 100 patients (42 with PPROM and 58 control group). RESULTS: Umbilical artery resistance index and systolic/diastolic (S/D) ratio were not different in PPROM cases and the control group (0.59 vs 0.58, 2.55 vs 2.43, respectively). Increased duration of membrane rupture had no effect on Doppler velocimetry. In patients with PPROM longer than 5 days, resistance index was 0.60, and systole/diastole ratio was 2.58; in patients with PPROM shorter than 5 days, resistance index was 0.58 and systole/diastole ratio was 2.52. There was no difference between two groups regarding Doppler findings. CONCLUSION: The presence of PPROM and the duration of PPROM have no effect on umbilical artery hemodynamic parameters.